Efektivitas Pembelajaran Berbasis Aplikasi Plickers sebagai Alat Evaluasi Formatif terhadap Hasil Belajar Siswa 113 Palembang Kelas IV - Tesha Mutiara Mulia; Susanti Faipri Selegi; Yasir Arafat (SENTRI: Jurnal Riset Ilmiah, 2026)
The integration of technology into educational assessment has become an important strategy for enhancing the effectiveness of the teaching and learning process, particularly in formative assessment practices that are still predominantly conducted through conventional methods. This study aimed to examine the effectiveness of Plickers application-based learning as a formative assessment tool on the learning outcomes of fourth-grade students at SD Negeri 113 Palembang. The study employed a quantitative approach using a true experimental design with a posttest-only control group design. The population consisted of 225 fourth-grade students, while the sample comprised 74 students selected through simple random sampling, including 38 students in the experimental class and 36 students in the control class. Data were collected through achievement tests and documentation and analyzed using normality tests, homogeneity tests, and an Independent Sample t-test. The results revealed that the experimental class achieved a higher mean posttest score (77.89) than the control class (70.33). More importantly, the Plickers group demonstrated a substantially higher learning mastery rate, with 81.58% of students achieving mastery compared to only 33.33% in the conventional control group, highlighting the considerable pedagogical advantage of technology-assisted formative assessment. Hypothesis testing indicated that the calculated t-value (3.180) was greater than the critical t-value (1.666) at a significance level of 0.05, resulting in the rejection of the null hypothesis and acceptance of the alternative hypothesis. These findings demonstrate that the Plickers application is effective as a formative assessment tool, as it improves students’ learning outcomes, facilitates immediate feedback, and creates a more interactive and engaging learning environment.